Relation between BMI, Total Leukocyte count and C Reactive Protein in Preeclampsia - Zaima Ali, Saima Zaki, Atiqa Khalid, Sadia Ahmad, Uzma Zafar, Shaheena Naz, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To check the correlation of Body Mass Index (BMI) with Total Leukocyte count (TLC) and C Reactive Protein (CRP) levels in preeclamptic and normotensive pregnant women. Methods: It was a comparative cross sectional study with 120 participants divided into two groups with 60 diagnosed cases of preeclampsia and 60 healthy pregnant women with normal blood pressure. The samples were collected in the third trimester of pregnancy. All the participants were in the range of 20-40 years of age and had a BMI within 18-25kg/m2. Results: TLC and BMI were significantly high in the preeclamptic group (p value <0.001). BMI correlated positively with both systolic and diastolic blood pressure (p value <0.05). A positive correlation at a significant p value of < 0.05 was observed between BMI and CRP levels. Moreover, BMI correlated with TLC at a statisticaly significant level (p value < 0.05). Conclusion: The study concludes that BMI is related to CRP levels as well as TLC in pregnancies complicated with PE. High BMI in the preeclamptic group highlights the role of adipose tissue as a source of systemic inflammation. In addition to placental dysfunction adipose tissue might contribute to the systemic inflammation due to superfluous production of inflammatory mediators.